FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA STMIK KAPUTAMA UNTUK BERWIRAUSAHA - Indah Ambarita; Iis Joice Susanti Marpaung (Universitas Methodist Indonesia, 2019)
The objective of the study was to find out the factors that influence the interests of STMIK Kaputama students to become entrepreneurs. The study type used descriptive qualitative and explanatory survey research. The data sources of this research were primary and secondary data. The population in this study was 419 students of STMIK Kaputama class of 2015 and 2016 who have taken entrepreneurship class, and 205 of them were used as the samples, taken by using a proportional stratified random sampling technique. The data were gathered by conducting a documentary study and distributing questionnaires. In this study, the answers to closed questions would be measured using a Likert scale. The variables would be measured and translated into indicator variables, the indicators were used as benchmarks for compiling instrument items which could be questions or statements. The analysis of the data used was descriptive analysis with a correlation regression analysis model using the SPSS program. The result of the study showed that personality has a significant effect on the interest of STMIK Kaputama students in entrepreneurship. Leadership has a significant effect on the interest of STMIK Kaputama students in entrepreneurship. Environmental has a significant effect on interest of STMIK Kaputama students in entrepreneurship. Entrepreneurship education has a significant effect on the interest of STMIK Kaputama students in entrepreneurship.